2014
DOI: 10.1061/(asce)cc.1943-5614.0000432
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of Concrete Bridge Decks Cast on GFRP Stay-in-Place Structural Forms

Abstract: The first part of the thesis addresses the fatigue performance of concrete bridge decks with GFRP stay-in-place structural forms replacing the bottom layer of rebar. The forms were either flat plate with T-up ribs joined using lap splices, or corrugated forms joined through pinand-eye connections. The decks were supported by simulated Type III precast AASHTO girders spaced at 1775mm (6ft.). Two surface preparations were examined for each GFRP form, either using adhesive coating that bonds to freshly cast concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Several FRP stay-inplace formwork configurations for decks have been proposed and investigated in previous studies. Flat plates with T-shape ribs (Oliva et al 2008, Bank et al 2010, Nicoletta et al 2019), flat plates with perforated rib connectors (Zuo et al 2018a, b), flat plates stiffened by bonded hollow square sections (Dieter et al 2002, Alagusundaramoorthy et al 2006, Hanus et al 2009, corrugated plates (Honickman and Fam 2009, Liu et al 2011, Fam and Nelson 2012, He et al 2012, Richardson et al 2014, a plate attached to the bottom of grid reinforcements (Ringelstetter et al 2006, Fang et al 2016, and pultruded hollow box sections with moulded grating (Gai et al 2013) are examples of FRP stay-in-place formworks. Cost analysis of reinforced concrete bridge decks with FRP stay-in-place formworks showed a 24% ~ 57% project cost reduction when compared to conventional concrete bridge decks (Berg et al 2006, Ringelstetter et al 2006, Matta et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Several FRP stay-inplace formwork configurations for decks have been proposed and investigated in previous studies. Flat plates with T-shape ribs (Oliva et al 2008, Bank et al 2010, Nicoletta et al 2019), flat plates with perforated rib connectors (Zuo et al 2018a, b), flat plates stiffened by bonded hollow square sections (Dieter et al 2002, Alagusundaramoorthy et al 2006, Hanus et al 2009, corrugated plates (Honickman and Fam 2009, Liu et al 2011, Fam and Nelson 2012, He et al 2012, Richardson et al 2014, a plate attached to the bottom of grid reinforcements (Ringelstetter et al 2006, Fang et al 2016, and pultruded hollow box sections with moulded grating (Gai et al 2013) are examples of FRP stay-in-place formworks. Cost analysis of reinforced concrete bridge decks with FRP stay-in-place formworks showed a 24% ~ 57% project cost reduction when compared to conventional concrete bridge decks (Berg et al 2006, Ringelstetter et al 2006, Matta et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…According to these researchers, the slabs performed well compared to the Eurocode serviceability limit states, even with conservative loading and contact areas. Richardson et al [ 36 ] studied the fatigue of concrete decks with GFRP stay-in-place forms by performing static and fatigue testing on the specimens. These researchers found that the decks built this way can withstand at least three million cycles with appropriate performance under service load.…”
Section: Introductionmentioning
confidence: 99%